MONITORING DAN EVALUASI PENGGUNAAN OBAT PADA PASIEN TERAPI GAGAL GINJAL KRONIK DI RUMAH SAKIT UMUM SEMBIRING DELI TUA - Batubara, Saiful; Tarigan, Palas; Chantika, Ike (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2023)
Chronic kidney failure is an interventional disease, which means that the patient only maintains existing kidney function and this disease is irreversible, meaning it cannot return to normal. Thus, chronic kidney failure is closely related to a rational treatment process and a healthy lifestyle. Therefore, it is necessary to study patterns of monitoring and evaluating drug use in patients with chronic kidney failure therapy at Sembiring Deli Tua General Hospital. This study aims to determine the lifestyle of second chronic kidney failure patients to determine the effect of chronic kidney failure patients' lifestyle on further improvement of kidney function. To determine rational drug use at Sembiring Deli Tua General Hospital using four aspects, namely right drug, right patient, right indication and exact last dose to see and know the distribution of chronic kidney failure to patient characteristics in the form of age, sex, disease complications, complaints and stage of chronic kidney failure patients at Sembiring General Hospital. Lifestyle monitoring was carried out in April-May 2023 in the hemodialysis room using a sample questionnaire that was taken as many as 30 respondents using a descriptive method. Then, an evaluation of drug use was taken from the medical record data of chronic kidney failure patients from September to December 2022 using a retrospective method. A sample of 30 patients according to the study inclusion criteria. The lifestyle of chronic kidney failure patients is in accordance with the provisions, and there is a relationship between the lifestyle of chronic kidney failure on the improvement of kidney function indicators are blood pressure, hemoglobin, urea and creatinine. Evaluation data on drug use in patients with chronic kidney failure in terms of four aspects including (100% right patient), (43.33% right drug), (83.33 place of indication), (80% right dose). patient characteristics in the form of age at most 46-55 years, the dominant sex is Male, complications of diseases namely hypertension then diabetes sequence When COPD, the most common complaint is lower abdominal pain, and the most common stage of chronic kidney failure patients is stage 3 at Sembiring General Hospital.